Chemical properties of dadih from Tanjung Bonai Regency, Tanah Datar District, West Sumatera, Indonesia. Issue 1 (November 2021) - Aritonang, S N; Roza, E; Yetmaneli,; Sandra, A
Abstract: Dadih derive from buffalo milk which is put into a bamboo tube and covered with banana leaves or plastic and then fermented at room temperature for 1-2 days until it forms lumps. This study aims to determine the nutritional value content (protein, fat, moisture content, pH and acidity). The research method is descriptive method and laboratory analysis. The sample used as material for this research is dadih from 5 farmers in Tajung Bonai Regency, Tanah Datar Regency. The results showed that the protein content for Dadihs ranged from 5.08-7.08%, fat content 5.57-8.09%, water content 72.38-78.74%, pH 4.4-4.9 and acidity 1.26-1.51%. From this research, it is concluded that the Tanjung Bonai Dadih has good nutritional value.